Comparison of microbial culture, metagenomic next-generation sequencing and droplet digital polymerase chain reaction methods for pathogen detection in patients with neurosurgical central nervous system infection - Yu, Hai; Liang, Dong; Ding, Xiangqian; Gao, Han; Fan, Guoyuan; Song, Yan; Sun, Shoujia; Huang, Qibing; Liu, Shili; Zhang, Zeli (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundNeurosurgical central nervous system infections (NCNSIs) are one of the most common complications in neurosurgical patients, followed by neurosurgery itself, trauma, implants or infection need to be treated by surgery. However, the diagnosis of NCNSIs continues to pose a significant challenge. The primary objective of this study was to comprehensively assess the diagnostic performance of metagenomic next-generation sequencing (mNGS) and Multiplex Droplet Digital PCR (ddPCR) in elucidating the microbiological etiologies underlying NCNSIs in affected patients.MethodsData on 127 enrolled NCNSIs patients were collected from Emergency Neurosurgical Intensive Care Unit at Qilu Hospital of Shandong University from June 2022 to October 2024. The clinical record, cerebrospinal fluid or pus routine, biochemical tests, microbial smear and culture, mNGS and ddPCR results, time to positive culture(TTPC), time from sample harvesting to final positive results (THTR) obtained by the physician, turn-around time for mNGS and ddPCR, and follow-up data were collected and analyzed.ResultsA total of 127 patients were enrolled in this study. In comparison to the positive rate achieved by traditional culture method (59.1%) in diagnosing NCNSIs, the overall pathogen detection rates of mNGS and ddPCR were markedly elevated (86.6%, p<0.01 and 78.7%, p<0.01, respectively). Notably, the administration of empiric antibiotics did not significantly influence the positive detection rates of either mNGS or ddPCR. When stratified by infection type, mNGS and ddPCR demonstrated notably higher positive detection rates in three specific categories of NCNSIs-ventriculitis, intracranial abscess, and implant-associated infections-compared to meningitis. Among the 127 patients, 37 (29.1%) tested positive via mNGS but negative via microbial culture, whereas 11 patients were positive via mNGS but negative via ddPCR. The mean TTPC for microbial culture was 15.1 ± 10.4 hours. Furthermore, the mean THTR for microbial culture, mNGS and ddPCR were 22.6 ± 9.4 hours, 16.8 ± 2.4 hours and 12.4 ± 3.8 hours, respectively. Importantly, ddPCR exhibited a significantly shorter THTR compared to mNGS (p<0.01).ConclusionmNGS and ddPCR hold the potential to substantially augment the diagnostic efficacy for NCNSIs patients. It is advisable that, in future clinical practice, mNGS and ddPCR be more extensively employed for the early and precise identification of pathogens in NCNSIs patients.